(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
In the modern world, sports games in general and table tennis in particular are no longer exclusively a means of physical education, somatic development, education of applied qualities and personal properties and health promotion and are turning into a field of intellectual activity for the implementation of innovative technologies. One of the most promising areas of innovation is the use of artificial intelligence in sports and pedagogical activities of coaches, teachers and their students. Artificial intelligence is increasingly being integrated into the processes of planning training sessions, analyzing technical, tactical and strategic actions, assessing the physical and mental capabilities of athletes and developing individual programs for their sports training. The use of artificial intelligence in game and applied sports that require a high level of coordination abilities, quick decision-making and flexible tactical and operational thinking, such as in such a type of sports games as table tennis, is especially effective. Modern innovative technologies allow creating digital simulations, using video analytics for in-depth analysis and analysis of sports games, recognizing errors in the technique of performing movements and predicting the behavior of opponents during the game. Artificial intelligence is also actively used in creating virtual coaches and adaptive simulators, which helps to improve the quality of athletes’ training for responsible competitions regardless of their level of qualification. The scientific article analyzes in detail modern approaches to integrating artificial intelligence into sports games using the example of table tennis, identifies the advantages and potential risks of using these innovative technologies, and outlines the prospects for further research in this and other related areas.